The Study of the Comparative Phraseological Structures of the Russian Language in Comparison with Uzbek - Sheralieva Mukhlisa Sharifjon kizi (Research Parks Publishers, 2021)
Authors are encouraged to study comparative phraseological units with similar units in Uzbek, taking into account national audiences. It should be noted that the study should focus on the phraseological units. That is separately mentioned and important attention should be paid their spiritual and grammatical features, as well as what kind of grammar category